2021
DOI: 10.1002/capr.12458
|View full text |Cite
|
Sign up to set email alerts
|

Crying in psychotherapy among Israeli patients and its relation to the working alliance, therapeutic change and attachment style

Abstract: Patients' crying in psychotherapy can, at times, be an indicator of a healing process and reflect patients' engagement. This study explored the relationships between Israeli patients' crying in therapy, the working alliance, therapeutic change and attachment styles, using similar procedures to the ones used by Genova et al. (2020; Psychotherapy, 58, 160) in a recent investigation of Italian patients. One hundred and thirteen patients completed an online survey in Hebrew about crying in therapy and self-repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(16 citation statements)
references
References 54 publications
2
14
0
Order By: Relevance
“…Regarding the direct relationship between clients’ crying experiences in therapy and the working alliance, our findings regarding the connection between clients experiencing their therapist as responding with compassion and support to their tears and the therapeutic alliance are consistent with both Genova et al (2021) and Katz et al (2022), providing further cross-cultural evidence for this potentially bidirectional relationship. That is, clients who experience their therapist as responding with support and compassion to their tears might experience a boost in their alliance, or a stronger alliance might impact the way that a client experiences how supportive or compassionate their therapist is to their tears.…”
Section: Discussionsupporting
confidence: 62%
See 4 more Smart Citations
“…Regarding the direct relationship between clients’ crying experiences in therapy and the working alliance, our findings regarding the connection between clients experiencing their therapist as responding with compassion and support to their tears and the therapeutic alliance are consistent with both Genova et al (2021) and Katz et al (2022), providing further cross-cultural evidence for this potentially bidirectional relationship. That is, clients who experience their therapist as responding with support and compassion to their tears might experience a boost in their alliance, or a stronger alliance might impact the way that a client experiences how supportive or compassionate their therapist is to their tears.…”
Section: Discussionsupporting
confidence: 62%
“…Further, clients perceiving their crying in therapy as an authentic and insightful moment, as well as feeling more understood and connected with their therapist after they had cried, was found to be correlated with reports of greater improvement in therapy. In a study using a similar methodology but with a sample of Israeli clients, Katz et al (2022) found that a higher number of reported patients' crying episodes in treatment was linked to positive therapeutic change. However, the authors note previous evidence that client crying in therapy's relation to the alliance or outcome is often not necessarily about quantity (i.e., the number of crying episodes) but rather about quality of that experience (i.e., the way these crying episodes are experienced and/or processed with the therapist).…”
Section: Crying Experiences In Therapy and Changementioning
confidence: 99%
See 3 more Smart Citations